Prevalence and associated factors of HIV among female sex workers in Eastern and Southern Africa: Systematic review and meta-analysis. - Tigabu Kidie Tesfie; Getaneh Awoke Yismaw; Bantie Getnet Yirsaw; Habtamu Wagnew Abuhay; Meron Asmamaw Alemayehu; Nebiyu Mekonnen Derseh; Gebrie Getu Alemu; Muluken Chanie Agimas (PLoS ONE)
Background Female sex workers (FSWs) are marginalized groups of the population who have limited access to healthcare and a higher risk of HIV infection due to biobehavioral and structural risk factors. Although it is known that the Eastern and Southern African region is affected by the highest HIV incidence and prevalence, understanding the burden among FSWs in the region remains limited. We aimed to assess the pooled prevalence and associated factors of HIV in this vulnerable population. Methods Relevant studies were searched on PubMed, Embase, Scopus, ScienceDirect, Hinari, African Journals Online (AJOL), Google, and Google Scholar. The searching mechanism was constructed using keywords identified by CoCoPop (Condition, Context, and Population) framework and medical subject heading terms to recruit studies published between January 1, 2015 and March 30, 2024. Observational studies that estimate the prevalence or incidence or associated factors of HIV among FSWs, even if FSWs were not the main focus of the study, were included. The quality of included studies was assessed using Joana Brigg's Institute checklist. Data were extracted and analyzed using STATA 17 software. To estimate the pooled effect sizes with their 95% confidence intervals, a random effect model was fitted. The I2 statistic was used to evaluate heterogeneity. Funnel plot and Egger's regression test were utilized to assess the small study effect. Publication bias was managed using trim-and-fill analysis. Subgroup and sensitivity analysis were considered to handle heterogeneity among studies. Results A total of 54 articles with 78,747 FSWs who had successful HIV biological test were included in the analysis. The pooled prevalence of HIV among FSWs in Eastern and Southern Africa was 36.0% (95% CI: 31.0%-41.0%). Regionally, the pooled prevalence was 59.0% (95% CI: 53.0%-64.0%) and 29.0% (95% CI: 25.0%-34.0%) in Southern and Eastern Africa, respectively. Age above 35 (POR = 7.35; 95% CI: 5.26, 10.28) and 25-34 years (POR = 2.91; 95% CI: 2.02, 4.21), being married (POR = 1.33; 95% CI: 1.07, 1.66), divorced (POR = 1.72; 95% CI: 1.39, 2.13), and widowed (POR = 2.70; 95% CI: 2.09, 3.49), primary education (POR = 1.29; 95% CI:1.08, 1.55), history of sexually transmitted infection (POR = 1.51; 95% CI: 1.20, 1.90), syphilis (POR = 2.57; 95% CI: 1.66, 3.98), Hepatitis B infection (POR = 2.60; 95% CI: 1.07,6.32), drinking alcohol (POR = 1.21; 95% CI: 1.01, 1.45) and injectable drug use before sex (POR = 1.75; 95% CI: 1.24, 2.47) were found significantly associated with the increased risk of HIV infection among FSWs. Conclusion These data suggest an urgent need to improve access to HIV prevention programs for FSWs. Providing behavioral interventions including reduction of alcohol and injectable drug use before sex, initiating tailored healthcare services, strengthening the psychosocial and legal support network, and fostering partnership might reduce the burden in the region. Clinicians could facilitate early detection and treatment of STIs, and Hepatitis B virus infection. Trial registration Protocol registration: The protocol for this systematic review and meta-analysis was registered in the PROSPERO with registration number CRD42024509200.